Embedding Heutagogy Principles into the Outcome-Based Education Curriculum - Silvia Mariah Handayani; Sani Susanti; Vidya Dwi Amalia Zati (Universitas Negeri Medan, 2026)
This study addresses the need to optimize student agency within structural frameworks by embedding heutagogical principles into the Outcome-Based Education (OBE) curriculum. The objective is to identify relevant heutagogical integration points and develop an updated framework for Community Education (Penmas). Utilizing a qualitative curriculum development method, the research was conducted within the Penmas Department at FIP Unimed in 2026. The research subjects comprised 25 specialized Penmas stakeholders from the North Sumatra region, selected via total sampling. Data collection was executed through a systematic literature review on OBE and heutagogy alignment. The data analysis technique utilized a qualitative matrix involving learning needs analysis, heutagogy material mapping, and structural framework synthesis. The results reveal that integrating self-determined learning shifts the educator's role to a facilitator and empowers students via double-loop learning, flexible pathways, and learner-generated content. In conclusion, this structural synchronization successfully equips Penmas graduates across all professional tracks with the metacognitive skills and innovative competencies required to thrive as autonomous, internationally competitive professionals in Society 5.0.